Application of Fuzzy Inference System using Tsukamoto technique as Strategy management (Case: Sales "Custom Case") - Rosida Vivin Nahari, Mars Caroline Wibowo, Syafrida Hafni Sahir, Nasrul, Muhammad Arifin (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to analyze the results of "custom case" sales predictions using intelligent systems with fuzzy techniques in digital printing. This research uses the location of "Arvi Digital Printing" which is a printing press in Pematangsiantar city that uses digital as well as producing "custom cases" of his own work. Data sources obtained through direct observation by interviewing the printing owner. The fuzzy technique used to solve this problem is the Tsukamoto method. The variables used are demand (X), inventory (Y), and production (Z). However, Arvi Digital Printing has not been able to determine how many custom cases that must be produced every week. Demand (X) has fuzzy set up, down, inventory (Y) has fuzzy set few, many and production (Z) has fuzzy set increase, decrease. The results of research using the Tsukamoto method can predict the number of "custom case" productions with input is demand (X) and inventory (Y) and output is production (Z) is 39 pcs a week with demand (X) 20 pcs and inventory ( Y) 60 pcs.